Reviewing the challenges and opportunities of digital technology integration in virtual education: Insights from MBA programmes in Iran - Laleh Karimi (Jurnal Inovasi dan Teknologi Pembelajaran, 2024)
The current study provides a comprehensive review of the integration of digital technologies in virtual education in Iran with a specific focus on MBA programmes. Drawing on research published from 2003 to 2022, the investigation seeks to identify major challenges, evaluate current practices, and offer recommendations for improving online MBA education within the Iranian context. An extensive search was conducted across databases such as Semantic Scholar, Google Scholar, Scopus, and Noormags, using keywords to select relevant studies focused on digital technology integration. The findings revealed that although digital technologies present opportunities for increased flexibility and educational innovation, their implementation in Iranian MBA programmes is hindered by inadequate technological infrastructure, limited lecturer training, and challenges in maintaining interactive and experiential learning environments. This review contributes to the existing literature by highlighting the unique institutional and geographic barriers faced by Iranian universities, providing a detailed analysis of these challenges, and proposing targeted strategies for overcoming them. Future research should prioritize the development of innovative solutions and the evaluation of their effects on the overall effectiveness of virtual MBA education in Iran